The Influence Of Using Short Stories on Students’ Vocabulary Mastery At The Eighth Grade Students of SMPN 1 Bulukumba - Ummul Habibah Nur; Nur Ina Syam; Syayyidina Ali (CV. Eureka Murakabi Abadi, 2026)
This study investigated the influence of using short stories on students’ vocabulary mastery among eighth-grade students at SMPN 1 Bulukumba. Vocabulary is one of the most essential components of language learning, as it supports students’ ability to understand, communicate, and develop other language skills. However, many students experience difficulties in acquiring and retaining vocabulary due to limited exposure to meaningful language contexts. Short stories are considered an effective instructional medium because they provide authentic language input, contextualized vocabulary, and engaging learning experiences that can enhance students’ understanding and retention of new words. This research employed a pre-experimental design using a one-group pre-test and post-test approach. The population of the study consisted of eighth-grade students at SMPN 1 Bulukumba. The sample was selected using a total sampling technique and involved 25 students. Data were collected through multiple-choice vocabulary tests administered before and after the implementation of short-story-based learning activities. The tests were designed to measure students’ vocabulary mastery and determine the effectiveness of short stories as a teaching medium. The results of the study revealed a significant improvement in students’ vocabulary mastery after the treatment. The mean score of the pre-test was 59.6, while the mean score of the post-test increased substantially to 90.4. Furthermore, the statistical analysis showed that the calculated t-test value was 10.14, which was higher than the t-table value of 2.06. As a result, the null hypothesis (H₀) was rejected and the alternative hypothesis (Hₐ) was accepted. These findings indicate that the use of short stories had a positive and significant effect on students’ vocabulary mastery. Therefore, short stories can be considered an effective and engaging teaching medium for improving vocabulary learning among junior high school students.